Interaction between the basolateral amygdala and dorsal hippocampus is critical for cocaine memory reconsolidation and subsequent drug context-induced cocaine-seeking behavior in rats - Wells, Audrey M. (Cold Spring Harbor Laboratory Press, 2011)
Contextual stimulus control over instrumental drug-seeking behavior relies on the reconsolidation of context-response-drug associative memories into long-term memory storage following retrieval-induced destabilization. According to previous studies, the basolateral amygdala (BLA) and dorsal hippocampus (DH) regulate cocaine-related memory reconsolidation; however, it is not known whether these brain regions interact or independently control this phenomenon. To investigate this question, rats were trained to lever press for cocaine reinforcement in a distinct environmental context followed by extinction training in a different context. Rats were then briefly re-exposed to the cocaine-paired context to destabilize cocaine-related memories, or they were exposed to an unpaired context. Immediately thereafter, the rats received unilateral microinfusions of anisomycin (ANI) into the BLA plus baclofen/muscimol (B/M) into the contralateral (BLA/DH disconnection) or ipsilateral DH, or they received contralateral or ipsilateral microinfusions of vehicle. They then remained in their home cages overnight or for 21 d, followed by additional extinction training and a test of cocaine-seeking behavior (nonreinforced active lever responding). BLA/DH disconnection following re-exposure to the cocaine-paired context, but not the unpaired context, impaired subsequent drug context-induced cocaine-seeking behavior relative to vehicle or ipsilateral ANI + B/M treatment. Prolonged home cage stay elicited a time-dependent increase, or incubation, of drug-context-induced cocaine-seeking behavior, and BLA/DH disconnection inhibited this incubation effect despite some recovery of cocaine-seeking behavior. Thus, the BLA and DH interact to regulate the reconsolidation of cocaine-related associative memories, thereby facilitating the ability of drug-paired contexts to trigger cocaine-seeking behavior and contributing to the incubation of cocaine-seeking behavior.